Striped Catfish Oil and Turmeric Extract-Reduce Inflammation and Insulin Resistance on Metabolic Syndrom: A Review - Helvi Desi Mambaya; Muflihatul Muniroh; Muhammad Sulchan; Diana Nur Afifah (Postgraduate, University of Mataram, 2024)
Metabolic Syndrome is continuing to grow worldwide. Indonesia is no exception. High-calorie diets and physical inactivity trigger several pathways involved in metabolic syndrome. These include inflammation and insulin resistance. Associated with type 2 diabetes mellitus, cardiovascular disease, and death, metabolic syndrome is important. There is therefore a need for early intervention to reduce the complications of this disease. Striped catfish (Pangasius hypophthalmus) is one of the freshwater fish farmed in Indonesia. Turmeric (Curcuma longa Linn.) is also widely used in Indonesian food preparations. This review aims to focus on striped catfish oil and turmeric extract that positively affect inflammation and insulin resistance in the intervention of metabolic syndrome. This review shows that striped catfish oil contains omega-3 fatty acids (EPA and DHA), while turmeric extract contains flavonoids, tannins, and saponins. Based on the results of the review, it is known that bioactive compounds found in catfish oil and turmeric extract can be used as nutraceutical ingredients to intervene in metabolic syndrome.